STRATEGI PENINGKATAN CAPACITY BUILDING NELAYAN PENGOLAH HASIL TANGKAP SESUAI DENGAN SDGS KE 14 DI WILAYAH PESISIR KOTA BATAM - Chusnul Febriandini; Glenndy Lambang Prasetyadi Dupuy; Achmad Yasir Baeda (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2023)
Indonesia is a maritime country. Because of maritime conditions, many Indonesians make their living as fishermen. Like Batam City, which has a coastal and marine area of 2,950 km2 or a total area of 73.93 km2 (Batam in 2010 figures). The vastness of the sea in Batam City means that Batam residents depend on the sea and work as fishermen. Fishermen who live on the coast work day and night to go to sea to produce fish catches for resale. The economy of coastal communities in Batam City is still relatively low if it only depends on fishing. This makes the government strive to improve community welfare through various community empowerment programs with SDGs (Suistanable Development). One way is to make school mandatory up to high school. Apart from that, providing technological solutions for fishermen to improve the standard of living of communities on the coast and oceans. Keywords: Batam, fishermen, SDGs